IUTAM Symposium on Multiscale Modelling of Damage and Fracture Processes in Composite Materials Proceedings of the IUTAM Symposium held in Kazimierz Dolny, Poland, 23-27 May 2005 - Sadowski, Tomasz.; Sadowski, Tomasz. (Solid Mechanics and Its Applications, 2006)
The IUTAM Symposium on “Multiscale Modelling of Damage and Fracture Processes in Composite Materials” was held in Kazimierz Dolny, Poland , 23 -27 May 2005. The Symposium was attended by 48 persons from 15 countries. During 5 day meeting, 4 keynote lectures and 39 invited lectures were presented. This volume constitutes the Proceedings of the IUTAM Symposium. The main aim of the Symposium was to discuss the basic principles of damage growth and fracture processes in different types of composites: ceramic, polymer and metal matrix composites, cement and bituminous composites and wood. Nowadays, it is widely recognized that important macroscopic properties like the macroscopic stiffness and strength, are governed by processes that occur at one to several scales below the level of observation starting from nanoscale. Understanding how these processes influence the reduction of stiffness and strength is essential for the analysis of existing and the design of improved composite materials. The study of how these various length scales can be linked together or taken into account simultaneously is particular attractive for composite materials, since they have a well-defined structure at the nano, micro and meso-levels. The well-defined microstructural level can be associated with small particles or fibres, while the individual laminae can be indentified at the mesoscopic level. Moreover, the advances in multiscale modelling of damage and fracture processes to the description of the complete constitutive behaviour in composites which do not have a very well-defined microstructure, e.g. cementitious, bitumous composites and wood was analysed.